2015
DOI: 10.1111/trf.13017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nucleic acid amplification test on screening of blood donors in Northern Pakistan

Abstract: NAT has improved the safety of blood products at our transfusion institution. Confirmation of NAT results must always be done either on follow-up samples or on samples from the retrieved frozen plasma bag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…were female, with a mean age of 29 years (range, 18-60 years) (Niazi et al, 2015). Also agree with a study done in Suez Canal University Hospital Blood Bank125, 562 blood donors (84%), were males, compared to 23,819 16%females.…”
Section: Parameterssupporting
confidence: 89%
“…were female, with a mean age of 29 years (range, 18-60 years) (Niazi et al, 2015). Also agree with a study done in Suez Canal University Hospital Blood Bank125, 562 blood donors (84%), were males, compared to 23,819 16%females.…”
Section: Parameterssupporting
confidence: 89%
“…AFIT, a regional blood center located in northern Pakistan in the Punjab province, serves the armed forces hospitals in Rawalpindi and Islamabad, and civilian hospitals in the region [13]. A total of 267,918 blood donations were screened during the study of which 1.45% were reactive for HBsAg.…”
Section: Resultsmentioning
confidence: 99%
“…The Punjab Province in India is near the border of Pakistan where two recent minipool NAT blood screening studies reported similar (or even higher) HBV and HCV yield rates than in our study, although NAT confirmation testing procedures differed. The serologic reactivity (in mainly first‐time donors) in India and Pakistan is frequently not confirmed by repeat testing, or by testing for alternative markers .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our algorithm eliminated discriminatory testing in 57 (0·15%) ID‐NAT non‐RR (and likely false IR) donations. The complexity of our repeat testing algorithm could be significantly reduced by obtaining the discriminatory results during the initial screening itself (using multidye probe technology); however, based on our observations and those of other investigators , repeat testing with an alternate sample from the donor or donation remains a necessity. As mentioned earlier, studies from Pakistan and South Africa showing 37–59% false ID‐NAT RR results serve as a caution against using the result of a single minipool resolution test or repeat ID‐NAT (or discriminatory) tests on the primary screening tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation